House dust fungal communities’ characterization: a double take on the six by sixty by six (6 × 60 × 6) project - Amaro, Raquel (2016)
Fungi are a group of microbes that are found with particular incidence in the indoor environment. Their direct toxicity or capability of generating toxic compounds has been associated with a large number of adverse health effects, such as infectious diseases and allergies. Given that in modern society people spend a large part of their time indoors; fungal communities’ characterization of this environmental compartment assumes paramount importance in the comprehension of health effects. House dust